Rare c-KIT c.1926delA and c.1936T>G Mutations in Exon 13 Define Imatinib Resistance in Gastrointestinal Stromal Tumors and Melanoma Patients: Case Reports and Cell Experiments - Yan, Chi; Zhao, Chengzhi; Yang, Ke; Zhou, Hongyan; Jing, Limin; Zhao, Weixing; Dou, Wenguang; Xia, Qingxin; Ma, Jie; Wei, Bing; Guo, Yongjun (Frontiers in Molecular Biosciences, 2022)
Background: Target therapies play more and more important roles in gastrointestinal stromal tumors(GIST) and melanoma with the advancement of clinical drugs that overcome the resistance caused by gene mutations. c-KIT gene mutations accounted for a large portion of GIST patients, which was known to be sensitive or resistant to tyrosine kinase inhibitors. However, it remains elusive for the role rare mutations played in drug efficacy and progression-free duration. Methods: Two rare mutations were identified using sanger sequencing from the GIST and melanoma cases. Cell experiments were further carried out to demonstrate their role in the imatinib resistance. Results: c-KIT c.1926delA p.K642S*FS mutation in primary and recurrent GIST patient and c-KIT c.1936T>G p.Y646D point mutationin melanoma patient in exon 13 were first demonstrated to be novel targets resistant to imatinib agent. Conclusion: c-KIT mutations c.1926delA and c.1936T>G in exon 13 are clinically significant targets which exhibit resistance to imatinib. This study provides guidance to GIST and melanoma treatments.